TINJAUAN TENTANG KUALITAS PELAYANAN DI MASA PANDEMI COVID 19 PADA PUSKESMAS LOA DURI ILIR KECAMATAN LOA JANAN KABUPATEN KUTAI KARTANEGARA - Salasiah dan Siti Rohayati (DEDIKASI : Jurnal Ilmiah Sosial, Hukum, Budaya, 2021)
The purpose of this study was to determine the quality of service during the Covid 19 pandemic at Loa Duri Ilir Public Health Center, Loa Janan District, Kutai Kartanegara Regency, and to determine the inhibiting factors of service at Loa Duri Ilir Puskesmas, Loa Janan District, Kutai Kartanegara Regency. This research is a descriptive qualitative research. The focus of this research is Service Quality during the Covid 19 Pandemic at Loa Duri Ilir Puskesmas, Loa Janan District, Kutai Kartanegara Regency, by analyzing: Service Procedures, Service Time, Service Costs, Service Products and Service Provider Organizations and Inhibiting Factors for Services at Loa Puskesmas Duri Ilir, Loa Janan District, Kutai Kartanegara Regency. Data collection techniques include: Observation, Interview, Documentation, Literature Study, and Data Analysis used is an interactive data analysis model (Miles & Huberman). Based on the research results, it can be seen that the service quality during the Covid 19 pandemic at the Loa Duri Ilir Puskesmas, Loa Janan District, Kutai Kartanegara Regency is good enough in providing services to the community. Starting from service procedures that are in accordance with the Operational Standards and Procedures applied during the Covid 19 pandemic, Service time in providing services during the Covid 19 pandemic at Loa Duri Ilir Puskesmas is in accordance with the regulations recommended by the Regional Government and the Central Government, Service costs In accordance with what is obtained, service products in providing services to residents who seek treatment are in accordance with the expectations and needs of residents who receive services, Service provider organizations in the problem of providing services about complaints, suggestions, and criticism are very open. Only in service during a pandemic covid 19, constrained by service time reduced in accordance withregulations applicable and restrictions on medical treatment room due to their social distancing to prevent berkerumunan in one room in a long period of time.